DNA Methylation in Anopheles albimanus Modulates the Midgut Immune Response Against Plasmodium berghei - Claudio-Piedras, Fabiola; Recio-Tótoro, Benito; Condé, Renaud; Hernández-Tablas, Juan M.; Hurtado-Sil, Gerardo; Lanz-Mendoza, Humberto (Frontiers in Immunology, 2020)
Epigenetic mechanisms such as DNA methylation and histone post-translational modifications are fundamental for the phenotypic plasticity of insects during their interaction with the environment. In response to environmental cues, the methylation pattern in DNA is dynamically remodeled to achieve an epigenetic control of gene expression. DNA methylation is the focus of study in insects for its evolutionarily conserved character; however, there is scant knowledge about the epigenetic regulation in vector mosquitoes, especially during their infection by parasites. The aim of the present study was to evaluate the participation of DNA methylation in the immune response of Anopheles albimanus to a Plasmodium infection. For this, we first investigated the presence of a fully functional DNA methylation system in A. albimanus by assessing its potential role in larval development. Subsequently, we evaluated the transcriptional response to Plasmodium berghei of two mosquito phenotypes with different degrees of susceptibility to the parasite, in a scenario where their global DNA methylation had been pharmacologically inhibited. Our study revealed that A. albimanus has a functional DNA methylation system that is essential to larval viability, and that is also responsive to feeding and parasite challenges. The pharmacological erasure of the methylome with azacytidine or decitabine abolished the divergent responses of both mosquito phenotypes, leading to a transcriptionally similar response upon parasite challenge. This response was more specific, and the infection load in both phenotypes was lowered. Our findings suggest that DNA methylation may constitute a key factor in vector competence, and a promising target for preventing malaria transmission.